2023
DOI: 10.3390/su15065433
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Green Cooling: Exploring the Benefits of Sustainable Energy-Powered District Cooling with Thermal Energy Storage

Abstract: This paper examines the economic and environmental impacts of district cooling systems (DCS) that are integrated with renewable energy sources and thermal energy storage (TES). Typically, a DCS offers a highly efficient and environmentally friendly alternative to traditional air conditioning systems, providing cool air to buildings and communities through a centralized system that uses chilled water. However, the integration of renewable energy and thermal energy storage into these systems can further increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
(148 reference statements)
0
1
0
Order By: Relevance
“…Keskin and Soykan reported a significant reduction in energy consumption and carbon emissions for a PV-assisted combined cooling, heating & power (CCHP) system for data center and residential customers [42]. In a review paper, Al-Nini et al, described the reduced electricity bills and minimal carbon emissions as the major economic and environmental benefits of integrating solar PV into DC systems [43]. For a Croatian site case study, Novosel et al, demonstrated that the potential for PV and wind electricity can be effectively utilised in areas with significant penetration of DHC networks [44].…”
Section: Techno-economic Impactsmentioning
confidence: 99%
“…Keskin and Soykan reported a significant reduction in energy consumption and carbon emissions for a PV-assisted combined cooling, heating & power (CCHP) system for data center and residential customers [42]. In a review paper, Al-Nini et al, described the reduced electricity bills and minimal carbon emissions as the major economic and environmental benefits of integrating solar PV into DC systems [43]. For a Croatian site case study, Novosel et al, demonstrated that the potential for PV and wind electricity can be effectively utilised in areas with significant penetration of DHC networks [44].…”
Section: Techno-economic Impactsmentioning
confidence: 99%